PELATIHAN PENINGKATAN KREATIVITAS DAN DESAIN KOMUNIKASI DIGITAL PADA SMP NEGERI 1 TANJUNG PALAS UTARA - Awang Pradana; Yarbania Stesya Sikit. Y; Muhammad Yusuf; Arjuna Pramudya Renaldi; Agung Gunawan; Gilberd Lamuel Sihite; Asran Asran (LPPM Universitas Abdurrab, 2025)
Students at SMP Negeri 1 Tanjung Palas Utara face challenges in graphic design and digital communication, primarily due to limited technological facilities and a lack of instruction. To address this issue, students received training in Creativity, Design, and Digital Communication. This training enhanced their understanding and skills in using digital technology for creative and academic purposes. The training utilized several methods, including needs analysis, site surveys, material presentations, and hands-on practice. Students were taught the fundamental principles of graphic design, the use of Canva, and Virtual Reality (VR) technology as an interactive communication medium. The results showed that students improved their understanding of graphic design and digital communication, with some adapting more quickly than others. Out of ten interviewed students, eight were able to grasp the material well, while two faced difficulties due to limited practice time. Additionally, the evaluation revealed that the main obstacles to implementing technology-based learning in schools were limited facilities, such as a lack of computers and an unstable internet connection. Further training with an extended duration, improved infrastructure, and active teacher involvement in supporting technology-based learning are necessary. Collaboration with universities and external creative communities could also help expand students’ access to higher-quality digital education.